The research of fluorescent lamps’ resource characteristics to test forced mode - Кожушко, Григорій Мефодійович; Басова, Юлія Олександрівна; Кислиця, Світлана Григорівна (Technology audit and production reserves, 2014)
The article presents the results of endurance tests of compact fluorescent lamps (CFLs) in the mode of the frequent ignitions. Using the results of examinations of compact fluorescent lamps (CFLs) in combustion mode with frequent ignitions the method of foreseeing their average durability is proposed. Experimentally was established that one ignition for CFL with previously heated cathodes is equivalent to approximately 0,53 h combustion, and for lamps without preheated cathodes – 0,65. Using the methods different CFLs brands, presented on the market of Ukraine, were evaluated for duration of their average combustion length and compliance with EU Regulation 244/2009 concerning the number of temperate ignitions. It is shown that the majority of investigated lamps parties complies EU Regulation № 244/2009, but their foreseen durability is lower than that one which is declared by manufacturers. This technique can be used, to a certain extent, for the prediction of the medium duration of burning, although it requires further improvement. First of all a big comparative statistics rating of the lamps durability of different constructions by traditional and accelerated methods is needed.